2018
DOI: 10.1111/1755-0998.12935
|View full text |Cite
|
Sign up to set email alerts
|

Application of CRISPR/Cas9 to Tragopogon (Asteraceae), an evolutionary model for the study of polyploidy

Abstract: Tragopogon (Asteraceae) is an excellent natural system for studies of recent polyploidy. Development of an efficient CRISPR/Cas9-based genome editing platform in Tragopogon will facilitate novel studies of the genetic consequences of polyploidy. Here, we report our initial results of developing CRISPR/Cas9 in Tragopogon. We have established a feasible tissue culture and transformation protocol for Tragopogon. Through protoplast transient assays, use of the TragCRISPR system (i.e. the CRISPR/Cas9 system adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 97 publications
0
38
0
Order By: Relevance
“…Our hypothesis requires further study — an effect of pectin metabolism on inflorescence development has not been reported in Asteraceae. With an established CRISPR/Cas9 system in Tragopogon ( Shan et al, 2018 , 2020 ), the functions of related genes (such as genes encoding pectinesterase and polygalacturonase) could be rigorously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis requires further study — an effect of pectin metabolism on inflorescence development has not been reported in Asteraceae. With an established CRISPR/Cas9 system in Tragopogon ( Shan et al, 2018 , 2020 ), the functions of related genes (such as genes encoding pectinesterase and polygalacturonase) could be rigorously examined.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we successfully applied the CRISPR/Cas9 technology for the first time in chicory. CRISPR/Cas9 technology was already successfully used to knock out genes in other plants of the Asteraceae family such as salsify [40], lettuce [41] and dandelion [30]. Asteraceae as well as members of the Brassicaceae and Solanaceae are amenable to this biotechnological approach because of their high ability to regenerate [42].…”
Section: Discussionmentioning
confidence: 99%
“…The thermoinhibition gene NCED4 was successfully edited using CRISPR/Cas9 in diploid, self-compatible lettuce ( Lactuca sativa ) with editing stability and Cas9 segregation demonstrated in the next seed generation [ 24 ]. In both sexual diploid Tragopogon porrifolius and tetraploid Tragopogon mirus, a low-efficiency Agrobacterium -mediated transformation system was developed to examine CRISPR/Cas9 gene editing efficiency in T0 calli and regenerated shoots, however plants were not taken to the next generation [ 25 ]. In hexaploid self-incompatible Chrysanthemum morifolium, low-efficiency editing of an introduced fluorescent marker gene was observed [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure S5: Detection of the Cas9 transgene in 78/79 T1 progeny from T0 chimeric HPDS mutants. References [ 48 , 49 , 50 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%